Pengembangan LKPD Pembuatan Briket Kulit Kakao sebagai Bahan Ajar Siswa SMA - Septianti, Indri; Carolina, Hifni Septina (Al Jahiz, 2023)
Cocoa waste that is not handled seriously will cause environmental problems such as an unpleasant odor. Cocoa waste will have a significant role if used as alternative energy, namely briquettes. Utilization of cocoa shells into briquettes can be developed into LKPD teaching materials. This study aims to produce worksheets for making cocoa shell briquettes as teaching materials for high school students. The research method used is the research and development method (Research and Development/R&D). The results of the research that has been done show the feasibility of LKPD according to material experts and media experts. Material validation was carried out twice, so that an average score of 45 was obtained with a percentage of 90% and included in the "Very Good" category while media validation was carried out twice, so that an average score of 40 was obtained with a percentage of 80% and included in the category " Well". This is supported by the results of field trials from small group trials obtained an average score of 43.9 with a percentage of 87.8% so that it has a very good category and the results of the teacher's response obtained an average score of 44 with a percent value 88% has a very good category. Keywords: LKPD, Briquettes, Cocoa Skin